THE PLACE OF THE FASHION INDUSTRY IN THE STRUCTURE OF CREATIVE STUDIOS - BUDNIKEVICH, Iryna; DUZIAK, Kseniia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the role and place of the fashion industry in the structure of creative industries, which today are one of the fastest growing sectors of the economy, a source of creating added value and new jobs through the generation of ideas, production, promotion and sale of products created on the basis of cultural, creative, knowledge and intellectual resources.Summarized information about the contribution of creative industries to the development of world and national economies, to creating jobs and ensuring sustainable development. Based on the theoretical analysis of the definitions of the "Creative Economy" category proposed by domestic and foreign scientists, public and professional organizations, it was concluded that the unifying elements are: ideas, creativity, innovation, knowledge, intelligence, uniqueness, technology, sustainability, value. Researched approaches to defining the essence of creative industries (creative studios) as the basis of the creative economy. The features of creative industries are summarized: the subjects are creative companies that are directly or indirectly based on creativity, originality, talents and unique skills; carry value for the preservation of cultural heritage, national identity and reflection of local characteristics; meet many sustainability challenges and ESG factors; use of creative, cultural, knowledge and intellectual resources; use of intellectual property objects for the production of goods and services; the result of activity is also objects of intellectual property and copyright; a creative product has a high value, as it involves a significant contribution of ideas and work of a creative person; the creative product is the object of falsification, counterfeiting and "piracy"; creative industries create new consumer value, added value and jobs; a high share of the use of product and technological innovations; a significant entrepreneurial, innovative and marketing component. It was noted that the modern fashion industry is an important sector of the creative economy, which includes the development, production, promotion and sale of fashionable goods (clothing, shoes, accessories). A semantic analysis of the inclusion of fashion in the structure of creative industries according to various approaches has been carried out, which proves the presence of this industry in all classifications of creative industries. It was concluded that fashion is one of the dominant components of creative industries, a form of mass communication, a cultural industry, generates its own marketing and advertising technologies, a special "fashion product", professional and informal fashion communities that have their own opinion and form specific standards. It was concluded that the fashion industry should be considered as an element of the creative economy, a creative industry that combines developers and manufacturers of fashionable products, suppliers of resources (raw materials, information, intellectual, marketing, creative), innovations and technologies (FashTech), the sphere of promotion services, implementation and service.